Pemanfaatan Limbah Jerigen menjadi Safety Box di RSUD Wates Tahun 2016 - Chichi Rodes Agustin; Choirul Amri; Adib Suyanto (Poltekkes Kemenkes Yogyakarta, 2020)
Solid waste in the form of used jerrycans in Wates Local Public Hospital is comprised of twotypes, i.e. the 5 L jerrycan which was contained acid liquid and the 10 L jerrycan which was contained bicarbonate fluid. In a month, the number of used jerrycans may reach 300. The changeof the jerrycans into safety boxes is one of the innovations to take advantage of the existingjerrycan waste in the hospital. Eventhough those two substances contained in the jerrycan arealmost similar with infusion fluid, they are not classified as hazardous waste as long there is nocontact with patients. This study was aimed to know the receptivity of respondents, i.e. consistedof 38 nurses and 9 cleaning service officers, toward the safety boxes which made of cardboardand those which made of used jerrycan as well, by conducting a prospective designed survey.The data were analysed by using dependent t-test at ? = 0,05; and gained p-value less than0,01; which can be interpreted that the receptivity between the two types of safety box is significantly different. Therefore, the conclusion is the used jerrycans yielded by the hospital can beutilized to replace the existing cardboard safety boxes.